Answer:
23,24,26,27 sorry if you get it wrong
Answer:
rgvrgvtgbrgvrgbthrfvrgvrhgbthgrvgvrgvthbtrfvrgvrgvhtbvrgvrgvhbt
Step-by-step explanation:
Hello I hope this helps. I'm pretty sure this is the answer.
Part A: C
Part B: A
x = 3 + y Eqn(1)
y = -2x + 9 Eqn(2)
Let us solve the system of equations with the substitution method
x - 3 = y (Subtracting 3 from both sides of the Eqn(1))
Replacing y = x - 3 in Eqn (2), we have:
x - 3 = -2x + 9
x = -2x + 9 + 3 (Adding 3 to both sides of the equation)
x + 2x = 9 + 3 (Adding 2x to both sides of the equation)
3x = 12 ( Adding like terms)
x = 12/3 (Dividing by 3 on both sides of the equation)
x = 4
Replacing x=4 in Eqn(1), we have:
4 = 3 + y
4 - 3 = y (Subtracting 3 from both sides of the equation)
y=1
The answers are:
x= 4 and y=1
Answer:
D 26
Step-by-step explanation:
154+154=308
308-360=52
52 divided by 2
=26